Designing an Optimized Nanocomposite Film Comprising Hydroxypropyl Methylcellulose, Nanoclay, and Dill Essential Oil to Extend the Shelf Life of Eggs - Mohammad Faghei Shahrbabaki; Alireza Shahab Lavasani; Nazanin Zand; Leila Nateghi; Mohammad Reza Eshaghi (International Journal of Food Science)
The use of films in the food industry is very widespread, with a focus on improving the quality of packaging films using nanoparticles and essential oils. The aim of this study was to optimize the formulation of hydroxypropyl methylcellulose (HPMC) film by combining nanoclay and dill essential oil (DEO). The ideal values of nanoclays and essential oils were determined through response surface design and Design Expert software. The results showed that the responses of water vapor permeability and tensile strength of the film were affected by input factors (amount of nanoclay and amount of essential oil), and the final model was estimated to be 4.26 wt% of nanoclay and 1.70 V/w of DEO. The optimal film was produced and compared with the samples of HPMC film containing nanoclay and the control sample (film without nanoclay and DEO). The optimal sample had the lowest rupture force (428 N), the lowest water vapor permeability (146.91 g.m/m2.s.Pa∗1011), the lowest solubility in water (24.12%), and the highest antioxidant and antimicrobial activity (75 DPPH) compared to the other samples. In the second stage of the study, raw egg samples were coated with an optimal HPMC film, and their qualitative properties were investigated. It was observed that egg samples coated with optimal layer had the lowest weight loss (4%) and egg white pH (8.7), while the Haugh index (5.56) and egg yolk index (8.3) had the highest value in samples coated with optimal layer. The sensory evaluation of egg samples showed that the optimal samples had the highest score in flavor coefficient (5.3). Based on the results of this study, it can be stated that the use of HPMC film containing nanoclay and DEO has a significant positive effect on improving the quality properties of eggs (p<0.05).